2. Work in Progress: Tracing Autochthony in Athens and Boeotia. A comparative Case Study - Ioannis Mitsios (Teiresias Journal Online, 2024)
Ioannis MITSIOS (University of West Attica) Tracing Autochthony in Athens and Boeotia: A comparative Case Study